Selective Targeting of Vascular Endothelial YAP Activity Blocks EndMT and Ameliorates Unilateral Ureteral Obstruction-Induced Kidney Fibrosis - Ren, Yafeng; Zhang, Yuwei; Wang, Lu; He, Fuqian; Yan, Mengli; Liu, Xiaoheng; Ou, Yangying; Wu, Qinkai; Bi, Tao; Wang, Shiyuan; Liu, Jian; Ding, Bi-Sen; et al. (ACS pharmacology & translational science, 2021)
Kidney fibrosis is accompanied by vascular dysfunction. Discovering new ways to ameliorate dysfunctional angiogenesis may bypass kidney fibrosis. YAP (Yes-associated protein) plays a multifaceted role during angiogenesis. Here, we found that selectively targeting YAP signaling in the endothelium ameliorates unilateral ureteral obstruction (UUO)-induced kidney fibrosis. Genetic deletion of Yap1, encoding YAP protein, in VE-cadherin+ endothelial cells inhibited endothelial-to-mesenchymal transition (EndMT) and dysfunctional angiogenesis and improved obstructive nephropathy and kidney fibrosis. Treatment with the systemic YAP inhibitor verteporfin worsened kidney fibrosis symptoms because of its lack of cell specificity. In an attempt to identify endothelial-specific YAP modulators, we found that G-protein-coupled receptor coagulation factor II receptor-like 1 (F2RL1) was highly expressed in vessels after UUO-induced kidney fibrosis. The F2RL1 peptide antagonist FSLLRY-NH2 selectively blocked YAP activity in endothelial cells and ameliorated kidney fibrosis. Thus, selective antagonization of endothelial YAP activity might bypass kidney fibrosis and provide new avenues for the design of antifibrotic therapies.